Monsoon News: From Science to Storytelling - Subin, Paul (Taylor & Francis Group, 2026)
This essay is concerned with the study of journalistic vocabularies and tropes (or what is sometimes referred to as “vernaculars”) used in weather reporting, a domain that until recently was neglected in journalism studies. It interprets and thematizes the vernaculars employed in reporting on a dominant seasonal weather phenomenon in South Asia: the monsoon. As an atmospheric-aqueous phenomenon, the monsoon is central to the Indian subcontinent’s agriculture and daily life due to its association with rainfall. I focus on monsoon coverage in an India-based science newsmagazine, Down to Earth (DTE). Drawing on literature from interdisciplinary fields such as science and technology studies and media anthropology, this essay identifies several vernaculars at work in DTE’s monsoon reportage—from summarizing the findings of scientific studies in lay terms to retelling popular monsoonal myths in conversational formats; from portraying the monsoon-induced travails of grassroots communities with solemn gravitas to evoking cherished gastronomical memories related to the monsoon in personalized tones. The journalistic use of an array of vernaculars helped DTE bridge the longstanding divide between news as storytelling and news as information. DTE, furthermore, highlighted climate change as a proximate threat in its monsoon coverage.
Keywords: 25 Ciencias de la Tierra y del Espacio::2502 Climatología ::2502.07 Climatología regional; ODS 13 - Acción por el clima; Monsoon; seasonal journalism; vernacular; storytelling; weather reporting; Global South